Activation of α7 Nicotinic Acetylcholine Receptor Protects Against 1-Methyl-4-Phenylpyridinium-Induced Astroglial Apoptosis - Hua, Ye; Yang, Beibei; Chen, Qiang; Zhang, Ji; Hu, Jun; Fan, Yi (Frontiers in Cellular Neuroscience, 2019)
Astrocytes, as the largest population of glial subtype, play crucial roles in normal brain function and pathological conditions, such as Parkinson’s disease (PD). Restoring the functions of astrocyte is a promising new therapeutic target for PD. Astrocytes can express multiple types of neurotransmitter receptors, including functional α7 nicotinic acetylcholine receptor (α7nAChR). Previously, we found that a non-selective α7nAChR agonist nicotine exerted a protective effect against H2O2-induced astrocyte apoptosis via an α7nAChR-dependent. However, the molecular mechanism of the anti-apoptotic response of astroglial α7nAChR has not been studied. In the present study, using pharmacological inhibition and genetic knockout of α7nAChR, we assessed the anti-apoptotic effects of an α7nAChR agonist PNU-282987 in primary cultured astrocytes treated with 1-methyl-4-phenylpyridinium (MPP+). PNU-282987 promoted the viability of astrocytes, alleviated MPP+-induced apoptosis, and decreased the number of GFAP+/TUNEL+ cells. Meanwhile, PNU-282987 up-regulated the expression of the anti-apoptotic protein Bcl-2 and down-regulated the expression of the apoptotic protein Bax and cleaved-caspase-3. Moreover, the suppression of the JNK-p53-caspase-3 signaling may underlie the neuroprotective property of PNU-282987. Therefore, PNU-282987 ameliorate astroglial apoptosis induced by MPP+ through α7nAChR-JNK-p53 signaling. Our findings suggest that PNU-282987 may be a potential drug for restoring astroglial functions in the treatment of PD.